Defining the needs and preferences of patients with dry eye disease. Issue 1 (5th December 2019) - Asbell, Penny; Messmer, Elisabeth; Chan, Colin; Johnson, Gary; Sloesen, Brigitte; Cook, Nigel
Abstract : Objective: Dry eye disease is a multifactorial chronic disease, leading to ocular discomfort and visual disturbance with a substantial impact on quality of life. Therefore, the patient's perspective should be taken into account early in the drug development process. We have developed a step-by-step methodology based on the self-explicated conjoint approach to assess the needs and preferences of patients with moderate-to-severe dry eye disease. Methods and Analysis: Following a literature review and social media listening (step 0), qualitative phone call interviews were conducted with 12 patients (step 1). Patients' responses underwent content analysis and were coded, quantified and displayed as charts. Based on the emerging trends and attributes identified as relevant in steps 0 and 1, a quantitative online questionnaire was designed and conducted with 160 patients across four countries (step 2). Results: The online questionnaire was rated as easy/very easy to understand by 60% of respondents, 62% rated the survey as easy/very easy to complete and 71% rated it as interesting/very interesting. Treatment satisfaction was the most important aspect for patients, and the three most relevant attributes were as follows (with the most important indexed to 100%): 'treatment effectiveness on symptoms of dry eyes' (100%), 'frequency of treatment use' (96%) and 'how the treatment works' (95%). Conclusion: Our methodology was well received by patients, and the results will help inform future clinical trial development and discussions with health technology assessment bodies and regulators on unmet needs and product attributes that are of most value to patients with dry eye disease.